Intellectualization of national education system through universalization - Sosnitsky, A.V. (Искусственный интеллект, 2014)
The paper is dedicated to the problem of modern classical Education based on knowledge. This Educational system has, essentially, exhausted its potential owing to the limited biological ability of people to perceive new knowledge, which leads to multiple social problems and conflicts. It is obvious that further development of the Educational system should be based on the other fundamental principles that, first of all, make the resources of people’s thinking more active. But there is no adequate formal theory of animate (intellectual) phenomena for the calculation of such processes. The method of solving these problems by the application of Universe Model for a substantiated deduction of the concept of Education and absolutization of the whole system of derivative abstracts is shown in the paper. The Reform of the national Education system in four consistently developing stages is offered, the final of which is directed at making people genius by the achievement of maximum thinking by means of an approach to absolute properties of the Universe. The main principles of genius Education are deduced, which at professional pedagogical concrete definition can already be assumed today as the basis of the new organization of educational processes and didactic materials to them with the use of available electronic environments and means of training.